2016
DOI: 10.1002/anie.201605099
|View full text |Cite
|
Sign up to set email alerts
|

A Bispidine Iron(IV)–Oxo Complex in the Entatic State

Abstract: For a series of Fe(IV) =O complexes with tetra- and pentadentate bispidine ligands, the correlation of their redox potentials with reactivity, involving a variety of substrates for alkane hydroxylation (HAT), alkene epoxidation, and phosphine and thioether oxidation (OAT) are reported. The redox potentials span approximately 350 mV and the reaction rates over 8 orders of magnitude. From the experimental data and in comparison with published studies it emerges that electron transfer and the driving force are of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 42 publications
3
59
0
Order By: Relevance
“…[7] This reactioni sn either efficient nors elective but, for the environmenta nd therefore for environmental chemistry,i t is of enormous importance.T here is ad ifferencei nt he vital requirements for catalytic processes in living systems, industrial processes,a nd environmentally relevant abiotic reactions. [7] Preliminary mechanistic studies indicated that oxotransferf rom af erryl oxidant to the sulfoxide, obtained by the preceding sulfoxidation of met,i st he key step in producing CH 3 radicals.T hese radicals were trapped and characterizedb y EPR spectroscopy.B ispidine-based ferryl complexes have aw ell-understood oxygenation and oxidation chemistry, [9][10][11][12][13] and are therefore excellent models fort he catalytically active ferryl speciesa nd av aluable tool for the mechanistic evaluation of this interesting reaction. For industrial processes, substrate selectivity is generally not essential and the level of product selectivity is (slightly) less important than in natural systems but catalysts tability is crucial.…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…[7] This reactioni sn either efficient nors elective but, for the environmenta nd therefore for environmental chemistry,i t is of enormous importance.T here is ad ifferencei nt he vital requirements for catalytic processes in living systems, industrial processes,a nd environmentally relevant abiotic reactions. [7] Preliminary mechanistic studies indicated that oxotransferf rom af erryl oxidant to the sulfoxide, obtained by the preceding sulfoxidation of met,i st he key step in producing CH 3 radicals.T hese radicals were trapped and characterizedb y EPR spectroscopy.B ispidine-based ferryl complexes have aw ell-understood oxygenation and oxidation chemistry, [9][10][11][12][13] and are therefore excellent models fort he catalytically active ferryl speciesa nd av aluable tool for the mechanistic evaluation of this interesting reaction. For industrial processes, substrate selectivity is generally not essential and the level of product selectivity is (slightly) less important than in natural systems but catalysts tability is crucial.…”
Section: Introductionmentioning
confidence: 68%
“…All 13 C/ 12 Ci sotope ratios (d 13 Cv alues) are expressed in the conventional d notation in % vs. VPDB (Vienna PDB standard), defined as Equation (1): The GC-C-IRMS system consisted of ac ryogenic preconcentration unit directly coupled to aH P6 890 n GC (Agilent Te chnologies, Santa Clara, USA), which is connected to aD elta PLUS XL isotope ratio mass spectrometer (ThermoQuest Finnigan, Bremen, Germany) via an oxidation reactor (ceramic tube (Al 2 O 3 ), length 320 mm, 0.5 mm i.d., with oxygen activated Cu/Ni/Pt wires inside, reactor temperature 960 8C) and aG CC ombustion III Interface (ThermoQuest Finnigan).…”
Section: Ch 4 Measurementsmentioning
confidence: 99%
See 3 more Smart Citations